Management services : part 1 - Mejorada, Nenita D. (Makati City, Philippines : Goodwill Trading Co, Inc., 2000)
It was written to provide an adequate textbook on the subject. It may be used by anybody desirous of acquiring proficiency in the use of accounting information in the decision-making process.
Chapter 1. Introduction ; Management Accounting ; Controllership -- Chapter 2. Horizontal and Vertical Analysis of Financial Statements -- Chapter 3. Analysis of Variation in Gross Profit and Net Income; Earnings per Share -- Chapter 4. The cash flow statement -- Chapter 5. Splitting Semi variable Costs; CVP Analysis. -- Chapter 6. Corporate Planning and budgeting -- Chapter 7. Responsibility Accounting and Standard cost Variance Analysis.
Keywords: MANAGEMENT